2021
DOI: 10.1039/d1fo00078k
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soybean insoluble dietary fiber on prevention of obesity in high-fat diet fed mice via regulation of the gut microbiota

Abstract: Increasing evidence has shown that the gut microbiota plays an important role in preventing obesity; however, the mechanism by which insoluble dietary fiber (IDF) prevents high-fat diet (HFD)-induced obesity remains unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 47 publications
3
39
0
1
Order By: Relevance
“…To solve the problem, we prepared high purity insoluble dietary fiber from okara (Okara-HPIDF) by enzymatic method, which purity could exceed 90% [16], and proved that it had potential bioactivities. Meanwhile, we proved that Okara-HPIDF had certain functions, such as improving lipid metabolism and so on [17,18]. In the process of studying its relationship with the changes of the colonic environment, we found that Okara-HPIDF could significantly change the composition of colonic flora [18].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…To solve the problem, we prepared high purity insoluble dietary fiber from okara (Okara-HPIDF) by enzymatic method, which purity could exceed 90% [16], and proved that it had potential bioactivities. Meanwhile, we proved that Okara-HPIDF had certain functions, such as improving lipid metabolism and so on [17,18]. In the process of studying its relationship with the changes of the colonic environment, we found that Okara-HPIDF could significantly change the composition of colonic flora [18].…”
Section: Introductionmentioning
confidence: 92%
“…Meanwhile, we proved that Okara-HPIDF had certain functions, such as improving lipid metabolism and so on [17,18]. In the process of studying its relationship with the changes of the colonic environment, we found that Okara-HPIDF could significantly change the composition of colonic flora [18]. This means that Okara-HPIDF was fully fermented by microorganisms in the colon, which may lead to changes in structure, composition, functionality, and even bioactivities of Okara-HPIDF.…”
Section: Introductionmentioning
confidence: 93%
“…Appropriate regulation of satiety is one of the important factors that connects diet, eating behaviors (e.g., meal size), and health. Table 4 [121][122][123][124][125][126][127][128] includes eight examples of recent studies and reviews on microbiota and the regulation of satiety. This review describes the control of multiple regulatory factors affecting satiety that are embedded within the gut microbiome.…”
Section: Satietymentioning
confidence: 99%
“…Appropriate regulation of satiety is one of the important factors that connects diet, eating behaviors (e.g., meal size), and health. Table 4 [ 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 ] includes eight examples of recent studies and reviews on microbiota and the regulation of satiety.…”
Section: Who Behavioral Modification #1: Eat a Healthy Diet (In Spite Of The Microbiota-driven Sense Control)mentioning
confidence: 99%
“…Appropriate regulation of satiety is one of the important factors that connects diet, eating behaviors (e.g., meal size), and health. Table 4 [121][122][123][124][125][126][127][128] includes eight examples of recent studies and reviews on microbiota and the regulation of satiety. In a recent review, Rautman and de la Serre [121] describe the multi-level influences of gut microbiota on a variety of mechanisms (e.g., both peripheral and central) determining satiety.…”
Section: Satietymentioning
confidence: 99%